Determinan Kepuasan Pelanggan Pada Penyewaan Lapangan Centro Futsal Cabang Daan Mogot - Dwi Susanto; Mhd Ichwan Hamzah (Faculty of Economic and Business, 2016)
The Determinant of Customer's Satisfaction to Centro Futsal Branch of Daan MogotThe aim of this research is to analyze the determinat of consumer satisfaction at Futsal Centro. This research is using multiple regression as tools of analysis. The independent variables of this research are service quality, promotion, and location. The result shows that the most influence in providing customer satisfaction is the location amounted to 0.364 and then followed by the variable of service quality amounted to 0.349 and followed by the promotion variable equal to 0.229. Then through the F test showed that the variables of service quality, well-deserved promotions and locations to test the dependent variable customer satisfaction on leasing futsal field. Through correlation R value is 0.811 or 81.1% and the determination coefficient value (R2) is 0.657, or 65.7.DOI: 10.15408/ess.v6i2.3574